Geophysical studies to delineate groundwater aquifer in arid regions: A case study, Gara Oasis, Egypt - NAZIH, Mohamed; GOBASHY, Mohamed; ARAFFA, Sultan; SOLIMAN, Khaled Soliman; ABDELHALIM, Ahmed (Contributions to Geophysics and Geodesy, 2022)
Groundwater is an important factor in establishing new urban communities, especially in coastal arid and semi-arid regions. Egypt is one of the world’s driest countries, with hyper-arid territory accounting for 86% of the total area and arid and semi-arid terrain accounting for the rest. The present work aims to demonstrate the powerful integration of geophysical techniques to assess groundwater potentiality and suitability in Gara Oasis (GO), which describes a good example of Egypt’s strategic southern extension of its arid north-western coast. Geophysical methods, including electrical resistivity and aeromagnetics, were used to evaluate groundwater resources. The study region reduced to pole total magnetic intensity map is subjected to digital filters that include derivatives, analytic signal, and tilt angle. The possible structures controlling the shallow and deep aquifers are delineated and integrated with geoelectric results. Moreover, two magnetic tomography sections are constructed to show the subsurface distribution of magnetic susceptibilities and formation boundaries. Ten vertical electric soundings (VESs) are measured and used in this study to construct four geoelectrical cross-sections. According to the results, Gara’s commonly calculated subsurface resistivity model comprises six major resistivity layers. The 5th layer, in particular, is composed of Fractured dolomitic Limestone and represents a possible promising shallow aquifer. Moreover, as evidenced by various magnetic data filters, the shallow (Miocene carbonate) and deep (Nubian sandstone) aquifers are structurally controlled and regulated by a system of faults or contacts. These contacts trends NW–SE, E–W, and NE–SW as common trends emerged from the total derivative and tilt maps. Results suggest that the central part (N–S zone) together with the western side of Gara, have the most notable aquifer possibility demanded future improvement strategies.